Experiencing stigma: Nepalese perspectives - Adhikari, SR; Pradhan, SN; Sharma, SC (Kathmandu University Medical Journal, 2009)
Background: Experiencing stigma by patients with mental illness in their day to day lives has substantial importance in treatment, compliance and quality of life. There is dearth of information and researches in experiences/ perceptions and coping of stigma in Nepal. Aims: The objective of this study was to find out experiences/ perceptions and coping of stigma and stigmatizations among patients with mental illness. Materials and methods: This is a retrospective, cross sectional study of patients admitted in psychiatry ward. Patients were assessed using self-report questionnaire which focused on beliefs about discrimination against mental illness, rejection experiences, and ways of coping with stigma. Patient’s socio demographic profiles were also assessed. Results: Fifty three patients completed questionnaire concerning various constructs of stigma. There were 29 male patients and 24 female patients. Majority (N=45; 84.9%) were of Hindu religion but there were mixed numbers regarding caste. Most of the patients were aware of the stigma associated with mental illness. There were experiences of rejection by family members and colleagues (N=23; 43.4%) and health care professional (N=16; 30.2%). There were strong perceptions of stigmatization felt by patients in different social circumstances. Though maintaining secrecy and avoidance/withdrawal of stigma provoking scenario were not experienced much, there was a strong sense of advocacy whenever there was any negative view of mental illness. Some of the questionnaire items in "perception", "rejection" and "coping" showed statistical significance (p=0.001). Conclusion: People with mental illness experience stigma during their course of illness and treatment and it is an important determinant for the relapse of symptoms and non-compliance to treatment. Despite experiencing stigma, patients were generally treated fairly by other people. Patients develop various mechanisms to cope with stigma, mostly secrecy and avoidance. Advocacy and anti-stigma campaign along with positive attitudes of health professionals play important role in decreasing stigmatizing experiences in patients. Key Words: Stigma, stigmatization, mental illness, coping, perception. doi: 10.3126/kumj.v6i4.1736 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 458-465